Osseous Coagulum Collected in Bone Traps: Potential for Bacterial Contamination and Methods for Decontamination - Etcheson, Aaron W.; Miley, D. Douglas; Gillespie, M. Jane (The Journal of oral implantology, 2007)
Because of its excellent osteogenic potential, autogenous bone is the preferred grafting material for dental procedures; however, bone collected in osseous coagulum traps is subject to contamination by oral bacteria. This study assessed bacterial contamination of osseous coagulum and tested treatments for reducing contamination. Fifty bone samples from patients undergoing implant osteotomy procedures were collected in osseous coagulum traps, divided into groups of 10, and rinsed with normal saline, 0.12% chlorhexidine, or 50 mg/mL tetracycline. Twenty control samples received no treatment. The bone samples were plated in triplicate on selective and differential media to assay aerobic and anaerobic bacteria and potential bacterial pathogens, including staphylococci, streptococci, enterics, and black-pigmented bacteria (BPB). Inoculations were performed with an Autoplate 4000, and plates were incubated at 37 degrees C either aerobically or in a Coy anaerobic chamber. Bacteria were isolated from all samples. In control samples, the mean colony-forming units (cfu) per milliliter of suspended osseous coagulum was 6.5 x 10(4) +/- 9.6 x 10(4) in aerobic cultures and 4.8 x 10(4) +/- 6.9 x 10(4) in anaerobic cultures. Viridans streptococci were isolated from 46 samples, with a mean of 2.9 x 10(4) +/- 4.1 x 10(4) cfu/mL. Enterics were in 16 samples with cfu ranging from 200 cfu/mL to 3.4 x 10(4) cfu/mL. Mannitol nonfermenting staphylococci were found in one sample at 106 cfu/mL. BPB were not isolated. A Mann-Whitney U test with significance set at P = .05 determined that the only statistically significant reductions in bacterial numbers occurred in tetracycline-treated samples of anaerobic bacteria (5-fold decrease, P = .02) and aerobic bacteria (6-fold decrease, P = .01). Tetracycline treatments effected a 7-fold decrease in streptococci, but the difference was not significant (P = .07). These data indicate significant bacterial contamination of bone collected in osseous coagulum traps and justify further research into methods for eliminating that contamination.